"They don't think it will ever happen to them": Exploring factors affecting participation in alcohol‐influenced aquatic activity among young Australian adults. (10th January 2021) - Calverley, Hannah L. M.; Petrass, Lauren A.; Blitvich, Jennifer D.
Abstract: Issue addressed: Young adults are over‐represented in alcohol‐related drownings in high‐income countries; however, little research has investigated their behaviours and decision‐making to inform prevention efforts. Methods: Semi‐structured interviews were conducted with 23 young Australian adults (aged 18‐24 years). Questions, informed by previous research, inquired about behavioural practices in aquatic contexts and influences on involvement in alcohol‐influenced aquatic activity. Interviews were transcribed verbatim. Thematic and interpretative phenomenological analysis followed. Results: Two main themes: personal and contextual awareness, and the impact of other people affected perceptions and involvement in alcohol‐influenced aquatic activity. Perceived control of situations and self‐confidence affected how these influences impacted individuals' involvement. Participants acknowledged some young adults likely overestimate their aquatic abilities. This awareness was not discussed in relation to their own capabilities. Conclusion: Drowning prevention efforts should inform young adults of the dangers of combining alcohol and aquatic activities, and make risks appear more immediate and applicable. Consideration should be given to measuring both perceived and actual aquatic abilities within various aquatic environments, to determine whether self‐reported perceived competence is an accurate proxy measure for actual aquatic ability. The influence of alcohol should also be highlighted. Steps are required for a positive shift in Australian norms of alcohol use in aquatic settings and the social and cultural attitudes towards this. So what?: This study provides new insight into young adults' perceptions and involvement in alcohol‐influenced aquatic activity. It enhances the evidence base for drowning prevention and health promotion practitioners and should inform more focused campaigns to prevent alcohol‐related drownings among young Australian adults.